Considerations for user consultation in a flow cytometry shared resource laboratory. Issue 3 (29th November 2021) - Graham, Amy; Korecky, Jena; Schultz, Eric; Gregory, Michael; Asosingh, Kewal
Abstract: User consultation is an essential first step in assuring high‐quality flow cytometric data. A central challenge to shared resource laboratory (SRL) staff is how to best guide new and current users to meet each projects' needs. One solution to this challenge is to follow a standard user consultation platform addressing all critical steps between the conception of the experiment and the actual acquisition of samples. Here we describe considerations to help an SRL understand the researcher's goals and how best the SRL staff can provide expert advice in a structured manner. User consultation has an educational nature, informing users about current best practices in cytometry that apply to their specific utilization. A consultation report also improves communication between the SRL, principal investigator, and lab members of the collaborating researcher. Development of best SRL practices is spearheaded by the ISAC SRL committee and this communication sets the foundation to initiate such report for user consultation. Implementation of best practices during user consultation will improve rigor and reproducibility in cytometry. Abstract :